Au(I)-catalyzed oxidative functionalization of yndiamides - Tong, Z; Garry, OL; Smith, PJ; Jiang, Y; Mansfield, SJ; Anderson, EA (American Chemical Society, 2021)
Yndiamides, underexplored cousins of ynamides, offer rich synthetic potential as doubly nitrogenated two carbon building blocks. Here we report a gold-catalyzed oxidative functionalization of yndiamides to access unnatural amino acid derivatives, using a wide range of nucleophiles as a source of the amino acid side chain. The transformation proceeds under mild conditions, is highly functional group tolerant, and displays excellent regioselectivity through subtle steric differentiation of the yndiamide nitrogen atom substituents.